2013
DOI: 10.1507/endocrj.ej13-0236
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in research on the distribution and function of NUCB2/Nesfatin-1 in peripheral tissues [Review]

Abstract: Abstract. Nesfatin-1 is a polypeptide derived from the posttranslational processing of the N-terminal fragment of nucleobindin 2 (NUCB2), that was originally identified as an anorexigenic hypothalamic neuropeptide. A number of reports have recently shown that NUCB2/Nesfatin-1 is widely expressed in various peripheral tissues, including those of the gastrointestinal tract where it may participate in various pathophysiological processes. One of its roles may be regulation of energy homeostasis. As a result, Nesf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…NUCB2/Nesfatin-1 showed widespread expression in the body, where it was mainly reported to participate in multiple pathophysiological processes like nocturnal feeding and body weight regulation [10]. Recently, a few studies revealed the correlation between NUCB2 and tumor development and possible mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NUCB2/Nesfatin-1 showed widespread expression in the body, where it was mainly reported to participate in multiple pathophysiological processes like nocturnal feeding and body weight regulation [10]. Recently, a few studies revealed the correlation between NUCB2 and tumor development and possible mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…NUCB2, as a precursor protein of nesfatin-1, was identified as a hypothalamus secreted protein originally and was found to be involved in feeding regulation in hypothalamic nuclei [10]. Subsequently, NUCB2 expression was found in peripheral tissues such as pancreatic islets, testis, stomach and adipose tissue [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies subsequently demonstrated NUCB2 expression in peripheral tissues such as stomach, pancreatic islets, testis, and adipose tissues [10][11][12][13], and a wide variety of basic cellular functions of NUCB2 including insulin release, adipocyte differentiation and myocardial performance has been proposed (reviewed in Cao et al [14]). Recently, possible roles of NUCB2 have been proposed in several human malignancies, which to date remain controversial [15][16][17][18][19][20].…”
Section: Cell Lines and Chemicalsmentioning
confidence: 99%
“…NUCB2 was first reported to be expressed in the arcuate nucleus, lateral hypothalamus, paraventricular nucleus and supraoptic nucleus of the hypothalamus (4,5). Following this, a number of studies have suggested that the primary peripheral source of NUCB2 was originated from stomach mucosa, and NUCB2 was also peripherally expressed in pancreas and fat tissues (7,8). In the hypothalamus, NUCB2 inhibits food intake and promotes body metabolism (4).…”
Section: Introductionmentioning
confidence: 99%